Exploring the Reasons for single-hood among Girls Aged Over 33 Years Living in Tehran: A Qualitative Study - Javad Yoosefi Lebni; Razieh pirouzeh; bahar khosravi; Morteza Mansourian (Kerman University of Medical Sciences, 2021)
Introduction: Both increase in the age of marriage and the prolonged singlehood among girls have become a major problem in Iranian society, leading to psychological and social harm. Therefore, the present study aimed to explain the reasons for singlehood among girls aged over 33 years living in Tehran.Methods: This study was a qualitative content analysis. The study population consisted of single girls aged over 33 years old in Tehran, Iran. A total of 18 unmarried girls aged over 33 years were purposefully selected and studied using semi-structured interviews. Conventional content analysis was used to analyze the data.Results: Data analysis resulted in 10 main categories including "university education", "obsession with the choice of their life's partner", "economic problems", "single girls' distrust of men", "instrumental view of marriage", "other alternatives to marriage", "appearance", "escaping from responsibility", "excessive parental strictness", and "increase in girls' expectations of their suitors".Conclusion: It is necessary to take steps to prevent the increase in the age of marriage among girls by applying appropriate interventions such as changing girls' attitudes toward marriage, educating parents to facilitate their adult children's marriage, providing welfare facilities, and employing young persons.